Validity and reliability of new made low pressure chamber "High Altitude Bed" - Yamamoto, M. (Japan Journal of Mountain Medicine, 1995)
Validity and reliability of new made low pressure chamber named "high altitude bed" were studied. It was made by Dr. I. Gamow for altitude training apparatus by bed rest condition including sleep. The structure of the chamber is very simple comparing to hitherto used low pressure chamber or room. The validity and reliability of the chamber were proved to be good by the experiments. The space of the chamber is narrow, but some kind of exercises such as leg extension were possible in it. Therefore the chamber is considered to be useful for altitude training both by bed rest as well as by exercise. Farthermore the chamber is useful not only for training apparatus but for experimental apparatus because of its high reliability.